The Influence of Artificial Intelligence (AI) Information Use on the Information Literacy of Students in the Library and Information Science Program at Universitas Negeri Padang - Disca Putri Alina; Marlini (Darul Yasin Al Sys, 2026)
The rapid development of artificial intelligence (AI) has transformed how university students access, manage, and utilize information for academic purposes. Despite the efficiency and convenience offered by AI-based information retrieval, its effective use requires adequate information literacy to ensure that generated content is critically evaluated and responsibly applied. This study examined the influence of AI-based information use on the information literacy of students in the Library and Information Science Program at Universitas Negeri Padang. A quantitative approach with a causal-associative design was employed, involving 79 students selected through proportionate stratified sampling. Data were collected using a structured questionnaire and analyzed through descriptive statistics, simple linear regression, a t-test, and the coefficient of determination using SPSS. The findings indicated that both AI-based information use and students’ information literacy were at high levels. The inferential analysis further demonstrated that AI-based information use had a positive and statistically significant effect on students’ information literacy. These results suggest that the effective and responsible use of AI can strengthen students’ capacity to identify, evaluate, manage, and apply academic information. This study contributes empirical evidence regarding the relationship between AI use and information literacy and provides practical implications for higher education institutions seeking to integrate AI literacy and information literacy into learning practices that promote critical, ethical, and responsible technology use.